Pregnancy‐induced changes in the pharmacokinetics of caffeine and its metabolites. (22nd December 2015) - Yu, Tian; Campbell, Sarah C.; Stockmann, Chris; Tak, Casey; Schoen, Katherine; Clark, Erin A. S.; Varner, Michael W.; Spigarelli, Michael G.; Sherwin, Catherine M. T.
Abstract: This study sought to assess the pharmacokinetic (PK) changes of caffeine and its CYP1A2 metabolites across the 3 trimesters of pregnancy. A prospective, multicenter PK study was conducted among 59 pregnant women (93.2% white) who were studied once during a trimester. One beverage with 30‐95 mg caffeine was consumed, and a blood/urine sample was collected within 1 hour postingestion. Concentrations of caffeine and its primary metabolites were quantified from serum and urine by LC‐MS/MS. There was a significant increase in dose‐normalized caffeine serum and urine concentrations between the first and third trimesters ( P < .05 and P < .01, respectively). Normalized theophylline concentrations also increased significantly in the third trimester in serum ( P < .001) and in urine ( P < .05). The caffeine urine/serum concentration ratio also increased in the last trimester ( P < .05). No significant difference was found in normalized paraxanthine or theobromine concentrations. This study identified decreased caffeine metabolism and an increase in the active metabolite theophylline concentrations during pregnancy, especially in the third trimester, revealing evidence of the large role that pregnancy plays in influencing caffeine metabolism.